Islamic Economic Perspective on The Implementation of Zakat in Promoting Economic Growth - Ainia, Zawida; Humaidi, Muchtim (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2024)
This study aims to find out how the implementation of zakat in encouraging economic growth. The research method used in this study is qualitative type with a descriptive approach method. The data collection technique uses library research techniques. To increase the economic growth of the community, what must be done by the BAZNAS institution is to emphasize the function of zakat. The inhibiting factors in the implementation of zakat to help increase economic growth are caused by several factors, namely, knowledge about the importance of zakat has not been well socialized, and there is still a lack of muzakki trust in amil zakat in zakat management. Furthermore, zakat also plays a role in economic growth. With the zakat given to mustahiq, the purchasing power of an item will increase and have an impact on increasing the production of a company which means there will be an increase in production capacity and can add to the country's economy aggressively.